IMPLEMENTASI MEDIA LEMBAR KERJA SISWA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Kurnia Putri, Dinda; Chaniago, Fransisko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the use of Student Worksheets (Lembar Kerja Siswa/LKS) in Islamic Religious Education classes at SMP Negeri 17 Jambi City, focusing on lesson planning, classroom implementation, assessment practices, supporting factors, challenges, and the efforts made to address those challenges. A qualitative descriptive approach was employed. Data were gathered through classroom observations, interviews, and document analysis, and were interpreted using the interactive analysis model of Miles, Huberman, and Saldana. The findings show that LKS has become part of the learning process and is incorporated into teaching modules that outline learning objectives, instructional materials, methods, and learning activities. Rather than serving as the primary instructional medium, LKS is used according to the needs of particular lessons and classroom situations. Student learning is assessed through worksheet activities, quizzes, question-and-answer sessions, essay assignments, and chapter tests. Adequate school facilities and the availability of LKS support its use in the classroom. However, not all students have access to their own worksheets, and differences in student participation remain a challenge. To respond to these conditions, teachers employ group work, shared worksheet use, classroom discussions, motivational strategies, and ice-breaking activities. Overall, LKS contributes positively to PAI learning, although further development is needed to encourage greater student participation and engagement.